A practical method for the preparation of total DNA from filamentous fungi - M. I. BORGES; M. O. AZEVEDO; R. BONATELLI JR.; M. S. S. FELIPE; S. ASTOLFI- FILHO (Fungal Genetics Reports, 1990)
Most methods of DNA preparation from fungi are time-consuming due to the need to first make protoplasts, expensive for chemicals such as cesium chloride, or suitable only for small scale preparations. We have developed a simple method for total DNA preparation, yielding a product of quality suitable for restriction digestion and library construction.